The Influence of Brand Awareness, Brand Image, and Brand Association on Brand Loyalty on iPhone Smartphones - Julfaturrahman Julfaturrahman; Henny Welsa; Budi Setiawan (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to examine the influence of brand awareness, brand image, and brand association on brand loyalty among iPhone smartphone users in Yogyakarta. This study used a quantitative approach by distributing questionnaires to 200 respondents. The results showed that brand awareness significantly influences brand image and brand association, but does not directly influence brand loyalty. Conversely, brand image and brand association have a significant influence on brand loyalty. Data analysis was conducted using SEM-PLS, including testing convergent and discriminant validity as well as construct reliability. These findings confirm that the indirect influence of brand awareness on brand loyalty is mediated by brand image and brand association.